Public acceptance of smart flood mitigation in Puchong - Chong, Jia Chen (2024)
In the past few years, flooding issue had become a frequent incident happened in the Puchong area. Although the government had allocated a huge budget in constructing the flood mitigation project, flooding issue still occurs frequently at the Damansara-Puchong Highway (LDP) located near the IOI Mall in Puchong. Therefore, it is crucial for the authorities to resolve the problem that govern the public immediately. In order to improve the implementation of Smart Flood Mitigation in Puchong, this research study focuses on investigating the public acceptance on Smart Flood Mitigation in Puchong. The first objective established in this research study is to identify the variables affecting the public acceptance on Smart Flood Mitigation in Puchong. In this research study, there are four independent variables that affecting the public acceptance on Smart Flood Mitigation in Puchong which are the Perception, Awareness, Readiness, and Preparedness. In order to measure the relationship and the impact of the independent variables towards the dependent variable, questionnaire survey was designed to collect the opinion of the respondents. A total of 137 samples were collected and undergo analysis by using the SPSS software and SmartPLS 4. This research showed that the public readiness and public preparedness ranked at the top two that caused impacts towards the public acceptance on Smart Flood Mitigation in Puchong. The analyzed results proved that the public readiness is significant affecting the public acceptance on Smart Flood Mitigation in Puchong. This research study helps the government to review in order to effectively implement the Smart Flood Mitigation in the Puchong area to fight against the flooding issues.